'NEW EXPERIMENTS IN CLASSICAL DANCE': KATHAK AND HAVELI MUSIC TERMS: ‘शास्त्रीय नृत्य में नवीन प्रयोग’: कथक एवं हवेली संगीत के पद - Verma, Vinita (International Journal of Research -GRANTHAALAYAH, 2015)
Music, that is, singing, playing and dancing, is supernatural and supernatural because of its nature. Spiritual music is the path leading to salvation through self-promotion by making life sacred. The dance has originated from the core of religion. Mystics have defined it as the basis of ecstasy. Dance and singing are said to be the best means of attaining salvation here. The Kathak dance, which is otherwise called 'Natvari dance', implies that Kathak dance relies mostly on Krishnacharitra for its expression. Uto Kathak has traditionally been exhibited on many verses, thumri, bhajans, etc. But for some years, a unique adornment of its own art is being done by art seekers through innovative experimentation in every field of art which is known as art (fans ) Is also well appreciated and accepted. Kathak dance, while staying within the limits of scripture, has always made new experiments in the field of emotion display. संगीत ंअर्थात् गायन, वादन और नृत्य अतिप्राचीन और ब्रह्मस्वरूप होने के कारण अलौकिक है । आद्यात्मिक संगीत जीवन को पवित्र बनाकर आत्मोन्नति द्वारा मोक्ष की ओर ले जानेवाला मार्ग है । नृत्य का आरंभ धर्म के मूल भाव से हुआ है । मनीषियों ने इसे परमानंद का आधार निरूपित किया है । नृत्य और गान को हमारे यहांॅं, मोक्ष प्राप्ति का श्रेष्ठतम साधन बताया गया है । कथक नृत्य जिसका अन्य नाम ही ‘नटवरी नृत्य’ है, इसका द्योतक है कि कथक नृत्य अपनी अभिव्यक्ति के लिए अधिकांशतः कृष्णचरित्र पर ही निर्भर है । यू ंतो कथक में परंपरागत अनेकों पद, ठुमरी, भजन इत्यादि पर भाव प्रदर्शन किया ही जाता रहा है किंतु कुछ वर्षो से कला के हर क्षेत्र में नवीन प्रयोग द्वारा अपनी अपनी कला का एक अपूर्व श्रृंगार कला साधकोें द्वारा किया जा रहा है जिसे कला (प्रशंसकों) द्वारा भी सहर्ष सराहा एवं स्वीकारा जा रहा है । कथक नृत्य ने भी शास्त्र की सीमा में रहते हुए भाव प्रदर्शन के क्षेत्र में नित नवीन प्रयोग किये है ।